2000
DOI: 10.1128/.68.11.6189-6195.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Glycosylphosphatidylinositol-Anchored Membrane Protein of Plasmodium yoelii Trophozoites and Merozoites Contains Two Epidermal Growth Factor-Like Domains

Abstract: Using sera from mice immunized and protected against Plasmodium yoelii malaria, we identified a novel blood-stage antigen gene, pypag-2. The 2.1-kb pypag-2 cDNA contains a single open reading frame that encodes a 409-amino-acid protein with a predicted molecular mass of 46.8 kDa. Unlike many characterized plasmodial antigens, blocks of tandemly repeated amino acids are lacking in the pypAg-2 protein sequence. Recombinant pypAg-2, comprising the full-length protein minus the predicted N-terminal signal and C-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It has been shown that several MSP-8 regions are antigenic during natural malarial infection and that MSP-8 recombinant proteins have a structural conformation recognized by human immune sera . MSP-8 also shows significant similarity with the protection-inducing sequence reported for the P. yoelii merozoite surface protein pypAg-2 . Comparing the two EGF-like domains in MSP-8 to pypAg-2 has revealed 55.3% identity in the first EGF-like domain and 58.3% identity in the second EGF-like domain, suggesting that the two proteins are homologues…”
Section: Merozoite Surface Protein (Msp) Familymentioning
confidence: 60%
See 1 more Smart Citation
“…It has been shown that several MSP-8 regions are antigenic during natural malarial infection and that MSP-8 recombinant proteins have a structural conformation recognized by human immune sera . MSP-8 also shows significant similarity with the protection-inducing sequence reported for the P. yoelii merozoite surface protein pypAg-2 . Comparing the two EGF-like domains in MSP-8 to pypAg-2 has revealed 55.3% identity in the first EGF-like domain and 58.3% identity in the second EGF-like domain, suggesting that the two proteins are homologues…”
Section: Merozoite Surface Protein (Msp) Familymentioning
confidence: 60%
“…17 MSP-8 also shows significant similarity with the protection-inducing sequence reported for the P. yoelii merozoite surface protein pypAg-2. 181 Comparing the two EGF-like domains in MSP-8 to pypAg-2 has revealed 55.3% identity in the first EGF-like domain and 58.3% identity in the second EGF-like domain, suggesting that the two proteins are homologues. 17 The MSP-8 gene has recently been disrupted in P. falciparum, thereby validating the specificity of the antibodies used in the study by Drew et al 182 and also demonstrating that MSP-8 does not seem to play an essential role in RBC cycle maintenance.…”
Section: Merozoite Surface Protein-7 (Msp-7)mentioning
confidence: 99%
“…It boosts insulin secretion [131] and is a growth and differentiation factor [132]. An equivalent has been found in mouse Plasmodium yoelii [133]. Phosphoglycane inositol is widespread in eukaryotes [134], plants, protozoa and mammals.…”
Section: Growth Factors and Differentiationmentioning
confidence: 99%
“…de Koning-Ward et al, 2007 3 Merozoite surface protein 8 (MSP8) is a glycosylphosphatidyl inositol (GPI)anchored membrane antigen originally identified in Plasmodium yoelii [1] and soon after in the human malaria parasite P. falciparum [2]. A distinctive feature of this protein is a C-terminal double epidermal growth factor (EGF)-like domain that resembles that seen in the dominantly expressed merozoite surface protein, MSP1.…”
mentioning
confidence: 99%
“…Hence, MSP8 may also be a target of protective antibodies and indeed it has shown considerable promise as a protective immunogen in the P. yoelii rodent malaria model system, both alone and in combination with MSP1-based antigens [1,6,7]. One interesting facet of these rodent malaria vaccine studies was the observation that 'breakthrough' parasites appear to have an increased preference for reticulocytes [6].…”
mentioning
confidence: 99%